Diagnostic Value of Cytokeratin 17 during Oral Carcinogenesis: An Immunohistochemical Study - Sirima Sanguansin; Theerachai Kosanwat; Rachai Juengsomjit; Sopee Poomsawat (International Journal of Dentistry)
Background. Little is known about the role of cytokeratin 17 (CK17) during oral carcinogenesis. CK17 expression in oral leukoplakia (OL), the most encountered oral potentially malignant disorders and oral squamous cell carcinoma (OSCC), remains very limited. To determine the role of CK17 during oral carcinogenesis and its potential diagnostic marker in oral premalignant and malignant lesions, this study evaluated CK17 expression in OL without dysplasia, OL with dysplasia, and OSCC. CK17 expression in these tissues was compared with those of normal oral mucosa (NOM). Additionally, the relationship between CK17 expression and clinicopathologic factors of OSCC was investigated. Methods. CK17 expression was evaluated in 186 samples consisting of 12 NOM, 33 OL without dysplasia, 58 OL with dysplasia, and 83 OSCC using immunohistochemistry. The proportion of positively immunostained cells was evaluated and scored. Results. CK17 was expressed in 8.3%, 54.5%, 74.1%, and 90.4% of NOM, OL without dysplasia, OL with dysplasia, and OSCC, respectively. NOM had a significantly lower CK17 score than OL with dysplasia (p=0.0003) and OSCC (p<0.0001). A significant association between CK17 expression and histopathologic differentiation of OSCC was found. Tumors with well differentiation had high CK17 expression compared with those of moderate and poor differentiation. Conclusion. CK17 was overexpressed in OL with dysplasia and OSCC, suggesting that CK17 plays a pivotal role in the development of premalignant lesions and OSCC. Of clinical significance, CK17 may be a good diagnostic marker for oral premalignant lesions and OSCC. Additionally, CK17 could be used as an objective tool to classify histopathologic grade in OSCC. The findings that CK17 expression is high in OSCC but low in NOM imply that CK17 may serve as a potential therapeutic target for OSCC.